1998
DOI: 10.1111/j.1398-9995.1998.tb03958.x
|View full text |Cite
|
Sign up to set email alerts
|

Latex allergy in spina bifida patients – prevention by primary prophylaxis

Abstract: Primary latex prophylaxis during surgery can prevent latex sensitization in young spina bifida patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 11 publications
4
29
0
2
Order By: Relevance
“…Cremer et al (55), in a pioneer study, recently, demonstrated that primary prevention could avoid the appearance of latex sensitization in children with spina bifida. The authors performed a prospective study with 2 years of duration, involving 12 newborns with spina bifida, which underwent surgery in a latex-free environment since the first day of their lives, verifying that none of these children were sensitized.…”
Section: Discussionmentioning
confidence: 99%
“…Cremer et al (55), in a pioneer study, recently, demonstrated that primary prevention could avoid the appearance of latex sensitization in children with spina bifida. The authors performed a prospective study with 2 years of duration, involving 12 newborns with spina bifida, which underwent surgery in a latex-free environment since the first day of their lives, verifying that none of these children were sensitized.…”
Section: Discussionmentioning
confidence: 99%
“…The use of powder-free gloves with decreased protein content especially led to a great reduction in airborne latex allergen [53] . Initiation of a primary NRL prophylaxis program around and during surgery, as well as anesthesia of all spina bifida patients, had a beneficial effect on the reduction of NRL sensitization [54] . The latest data finally show that in children with spina bifida who grew up completely latex-free from birth on, sensitization to NRL was 5% in comparison to 55% for a former non-latex-free group, and clinically relevant allergy decreased significantly from 37 to 1% [55] .…”
Section: Preventive Measures -Successful Avoidance Strategymentioning
confidence: 99%
“…4 The same authors observed no new sensitization after having established latexfree surgery and anesthesia. 5 Our study considers three time points.…”
Section: Latex Allergy In Spina Bifida: At the Turning Point?mentioning
confidence: 99%